A phase field investigation of dendrite morphology and solute distributions under transient conditions in an Al–Cu welding molten pool. (17th August 2016) - Wang, L.; Wei, Y.; Zhan, X.; Yu, F.
Abstract : A quantitative phase field model is developed to simulate dendrite morphology and solute distributions of the Al–4 wt-% Cu alloy in Gas Tungsten Arc Welding (GTAW) welding molten pool under transient conditions. The functions of temperature gradient and travel velocity are used to obtain transient conditions of the welding molten pool. Time evolutions of the dendrite morphology, solute distributions of different positions and interfaces are obtained. The dendrite growth process can be divided into four stages, namely linear growth, non-linear growth, competitive growth and short-term steady growth. The solute concentration near the primary dendrite tip region is the smallest, while solute concentration is larger in the front of plane crystals growth interface and the solute concentration in the liquid region among the primary dendrites is obviously the largest, where the solute segregation forms readily. For the given welding parameters, the dendrite morphology and the initial instability of solid/liquid interface agree well with the experimental result.